2020
DOI: 10.1177/0003702820906890
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profiling Investigation of Seawater Using Combined Multi-Optical Spectrometry

Abstract: Depth profiling investigation plays an important role in studying the dynamic processes of the ocean. In this paper, a newly developed hyphenated underwater system based on multi-optical spectrometry is introduced and used to measure seawater spectra at different depths with the aid of a remotely operated vehicle (ROV). The hyphenated system consists of two independent compact deep-sea spectral instruments, a deep ocean compact autonomous Raman spectrometer and a compact underwater laser-induced breakdown spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Since the monitoring of ionic composition is important for the characterization of waters, some authors have already used LIBS as a sensing system. 9,12 Popov et al 23 achieved a limit of detection (LOD) of 0.2 mg L −1 for Sr( ii ) in the direct analysis of natural waters under static conditions, demonstrating that the method provides accurate results in a concentration range from 1 to 20 mg L −1 , with a RSD of 12%. The authors also demonstrated that salinity has a strong influence on the plasma electron density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the monitoring of ionic composition is important for the characterization of waters, some authors have already used LIBS as a sensing system. 9,12 Popov et al 23 achieved a limit of detection (LOD) of 0.2 mg L −1 for Sr( ii ) in the direct analysis of natural waters under static conditions, demonstrating that the method provides accurate results in a concentration range from 1 to 20 mg L −1 , with a RSD of 12%. The authors also demonstrated that salinity has a strong influence on the plasma electron density.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy (LIBS) has been used as a promising analytical tool, proving to be efficient for the analysis of liquid samples. [10][11][12][13] LIBS is a type of spectroscopic technique that uses a laser for vaporization, atomization and excitation of samples in a plasma formed due to the lasermatter interaction, using optical emission for analytical purposes. 14 The technique presents an analytical approach with multi-element capability, in addition to minimal or nonexistent sample preparation and easy operation, being applied to solids, liquids and gas analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first deep ocean Raman in situ spectrometer system (DORISS) was reported in 2004 [ 1 ], researchers have established several underwater Raman systems and applied them to different in situ detection scenarios. The typical instruments include the upgraded DORISS II developed by Monterey Bay Aquarium Research Institute (MBARI) [ 2 ], the hybrid Raman insertion probe (Rip) developed by the Institute of Oceanology Chinese Academy of Sciences (IOCAS) [ 3 ], and the underwater Raman systems independently developed by the Ocean University of China (OUC) and the French Research Institute for Exploitation of the Sea (IFREMER) [ 4 , 5 , 6 , 7 , 8 ]. These systems have been deployed on ROVs for in situ detection of sediment pore water [ 9 , 10 ], deep-sea minerals [ 11 , 12 ], bacterial mats [ 13 ], methane hydrates [ 14 , 15 , 16 ], and the fluid of hydrothermal vents or cold seeps [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ocean University of China developed a compact 4000 m rated deep-sea LIBS system (LIBSea) by using the integrated design in 2015. The system has performed the detection of hydrothermal fluid in Manus area and the measurement of seawater profile with the diving of Faxian ROV [26,27]. The major metallic elements, Na, Ca, K, Mg, as well as Li, were clearly detectable in the spectra obtained at sea floor in the hydrothermal area, and the elemental profiles of LIBS signals of K and Ca were also obtained during the sea trials.…”
Section: Introductionmentioning
confidence: 99%